Improving the Stability of Organic–Inorganic Hybrid Perovskite Light‐Emitting Diodes Using Doped Electron Transport Materials. Issue 20 (25th October 2019) - Kim, Taejun; Kim, Jin-Hoon; Triambulo, Ross E.; Han, Hyowon; Park, Cheolmin; Park, Jin-Woo
Abstract : Perovskite Light‐Emitting Diodes In the ambient air, a novel N2 gas blowing step is applied during spin‐coating of the precursor solution to obtain uniform methylammonium lead bromide (MAPbBr3 ) perovskite nanocrystal films with fewer surface and interfacial defects than solution‐processed perovskite films. Furthermore, PEI‐ and PFN‐doped TPBi acted as passivation agents between the rough surface of the perovskite film and the electron transport layer. Consequently, the high surface work function of PEI‐ and PFN‐doped TPBi resulted in the reduced and balanced injection of electrons in the perovskite light‐emission layer (EML) of the PeLEDs, producing a higher luminance, also showed a longer lifetime. More details can be found in article number 1900426 by Taejun Kim, Jin‐Woo Park and co‐workers.